The Correlation between the Test Scores from Siriraj Preclinical Comprehensive Examination and National Licensing Examination Step 1 of the 3rd Year Medical Students of the Faculty of Medicine Siriraj Hospital - Sridathon, Nuttamon; Supaprasert, Pakanut; Noosen, Pirawan; Pongpaibul, Ananya; Trongwongsa, Therdkiat (Siriraj Medical Bulletin, 2020)
The Correlation between the Test Scores from Siriraj Preclinical Comprehensive Examination and National Licensing Examination Step 1 of the 3rd Year Medical Students of the Faculty of Medicine Siriraj Hospital Pakanut Supaprasert, B.A.*, Nuttamon Sridathon, B.Ed.*, Pirawan Noosen, M.S.*, Ananya Pongpaibul, M.D.** *Education Department, Division of Medical Education, **Department of Pathology, Faculty of Medicine Siriraj Hospital, Mahidol University, Bangkok 10700, Thailand. Abstract Objectives: This study aims to correlate between the test scores from Siriraj preclinical comprehensive examination (SiPC exam) and National Licensing Examination Step 1 (NL1)and GPA of the 3rd year Medical students from 2016 to 2018 academic year. Methods: The test scores from SiPC exam and NL1 of the 3rd year medical students and GPA were retrospectively recorded. Correlation analysis of between both test scores and correlation between GPA were performed. Results: 923 medical students from 2016-2018 were included. 876 students (94.13%) passed SiPC exam and 870 students (94.3%) passed NL1 examination at the first attempt. The correlation between SiPC exam and NL1 examination was 0.898. Most of the students (46.9%) had got the range of GPA 3.00 -3.49 . Correlation between test scores from SiPC exam and NL1 was 0.896. Correlation between GPA with test scores from SiPC exam and NL1 were 0.859 and 0.874, respectively. Conclusions: The test scores of the 3rd Medical student year 2016-2018 from SiPC exam and NL1 were highly related. GPA had good relationship with test scores of SiPC exam and NL1. Keywords: Preclinical comprehensive examination, National Licensing Examination Step 1, NL1, GPA, medical student